(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
Abstract The Parliamentary Commission of Inquiry is one of the most important instruments for parliamentary minorities and, consequently, for the maintenance of a democratic rule of law. Through this Commission, the Legislative Power has the possibility to investigate activity arising from its supervisory function. In this perspective, it is clear how partisan proportionality is necessary in the choice of members of that collegiate, in order to guarantee that the minority has effective participation in the works. At the end of the legislative inquiry, a document is prepared that will gather all the data collected in the investigation and that will be a fundamental piece for the competent public agencies to promote accountability. This is the final report, which must be seen as the result of the right of the parliamentary minority and, as a result of this characteristic, must be unique, and there is no need to talk about approval by the plenary or any other part of the respective Legislative House. The method adopted was the analytical-deductive one, using bibliographic, documentary and qualitative research. Keywords: Parliamentary Inquiry Commission, Investigative Function, Minorities, Final Report, Partisan proportionality.